Mechanism of Action of the Tungsten Dopant in LiNiO2 Positive Electrode Materials. Issue 6 (31st December 2021) - Geng, Chenxi; Rathore, Divya; Heino, Dylan; Zhang, Ning; Hamam, Ines; Zaker, Nafiseh; Botton, Gianluigi A.; Omessi, Roee; Phattharasupakun, Nutthaphon; Bond, Toby; Yang, Chongyin; Dahn, J. R.
Abstract: The addition of tungsten has been reported to greatly improve the capacity retention of Ni‐rich layered oxide cathode materials in lithium‐ion batteries. In this work, Ni(OH)2 precursors, coated with WO3 and also W‐containing precursors prepared by co‐precipitation followed by heat treatment with LiOH·H2 O, are studied. Structural analysi s and electron microscopy show that W is incorporated as amorphous Li x W y O z phases concentrated in all the grain boundaries between the primary particles of LiNiO2 (LNO) and on the surface of the secondary particles. Tungsten does not substitute for Ni or Li in the LNO lattice no matter how W is added at the precursor synthesis stage. Scanning electron microscopy (SEM) images show that adding W greatly suppresses primary particle growth during synthesis. In agreement with previous literature reports, cycling test results show that 1% W added to LNO can greatly improve charge–discharge capacity retention while also delivering a high specific capacity. The Li x W y O z amorphous phases act as coating layer on both the primary and secondary particles, restrict primary particle growth during synthesis and increase the resistance of the secondary particles to microcracking. Abstract : Direct observation shows the tungsten dopant in lithium nickel oxide exists as amorphous lithium tungstate phases concentrated in all the grain boundaries. Tungsten does not substitute for nickle or lithium in the lattice, regardless of how tungsten is added in the precursors. The tungstate phases restrict primary particle growth during synthesis and increase resistance to microcracking, significantly improving cycle life.